Beringharjo Market: Object and Tourist Attraction - Tiurmida, Nelly; Sugiyanto, Sugiyanto (MultiTech Publisher, 2023)
It primarily aims to understand how the Yogyakarta Government works to position Beringharjo as a tourist hotspot and pinpoint factors drawing in visitors. Using qualitative case study methods, it investigates the market's dynamics involving visitors, tourists, and traders. Data collection involved observation, interviews, and secondary sources, merging primary and secondary data via content analysis. Informant selection through purposive sampling ensured insights aligned with the study's objectives. The findings highlight extensive governmental efforts to enhance Beringharjo's appeal. Measures include organizing traders, setting up an ATM center, establishing a One-Stop Shopping Center, and meeting diverse visitor and tourist needs. The market offers traditional cuisine, batik, fashion, handicrafts, alongside facilities like escalators, places of worship, health clinics, and ample parking, all to augment its allure.